Arbuscular-mycorrhizal associations with apple plantations of different age groups in Himachal Pradesh - NARENDER K. BHARAT*, PRAVEEN MEHTA and (Indian Phytopathology, 2013)
Arbuscular-mycorrhizal fungi (AMF) are symbionts which live in association with the roots of many plant species. The associations are known to improve plant growth, nutrient uptake and defense mechanisms in plants including apple. The present investigations were conducted during 2009–2010 to find out spore population of AMF in different types of apple orchards in Shimla district of Himachal Pradesh, which is the main apple belt. During survey of apple orchards at Shimla hills, AM fungi were invariably found associated with apple plantation in all locations surveyed and the population of these fungi was observed high in old bearing orchards (20-35 years) followed in young (5-15 years) and minimum in unproductive senile orchards (above 40 years). Twelve AM fungal species under four genera viz., Glomus, Acaulospora, Gigaspora and Scutellospora were isolated and frequency of occurrence was high in case of Glomus spp. especially G. fasciculatum, G. mosseae and G. macrocarpum.